Dentinogenic Ghost Cell Tumor of the Peripheral Variant Mimicking Epulis. (12th October 2010) - Kumar, Uddipan; Vij, Hitesh; Vij, Ruchieka; Kharbanda, Jitin; Aparna, IN; Radhakrishnan, Raghu
Abstract : Dentinogenic ghost cell tumor (DGCT) is an uncommon locally invasive odontogenic tumor regarded by many as a variant of calcifying odontogenic cyst. The peripheral variant of this clinical rarity appears as a well-circumscribed mass mimicking a nonspecific gingival enlargement. Microscopic appearance of odontogenic epithelium admixed with focal areas of dentinoid formation and sheets of ghost cells giving the definitive diagnosis of dentinogenic ghost cell tumor imply that microscopic examination is compulsory for any gingival mass. Van Gieson histochemical stain further confirmed the nature of dentinoid-like material. A complete workup of a case of peripheral dentinogenic ghost cell tumor is presented in this paper and the current concept as well as the appraisal of literature is presented.